TRANSABDOMINAL OESOPHAGEAL TRANSSECTION AND PARAOESOPHAGOGASTRIC DEVASCULARIZATION FOR BLEEDING OESOPHAGEAL VARICES - Bekir KÜÇÜKKAYIKÇI; A. Tahir ERDEM; Aydın DALGIÇ; İsmet BARAN and Oskay KAYA (Turkish Journal of Gastroenterology, 2020)
-